Global Occupational Exposure to Blood and Body Fluids among Healthcare Workers: Systematic Review and Meta-Analysis. (3rd June 2022) - Mengistu, Dechasa Adare; Dirirsa, Gebisa; Mati, Elsai; Ayele, Dinku Mekbib; Bayu, Kefelegn; Deriba, Wegene; Alemu, Fekade Ketema; Demmu, Yohannes Mulugeta; Asefa, Yohanis Alemeshet; Geremew, Abraham
Abstract : Background . Occupational exposure to blood and body fluids has become a serious public health problem for healthcare workers and is a major risk for the transmission of various infections such as human immune-deficiency virus, hepatitis B virus, and hepatitis C virus. This systematic review and meta-analysis aims to determine the career time and previous one-year global pooled prevalence of occupational exposure to blood and body fluids among healthcare workers. Methods . For the review, the articles published in English were searched using the electronic databases (SCOPUS/Science Direct, PubMed, Web of Science, Google Scholar, CINAHL, MEDLINE, Cochrane Library, DOAJ, and MedNar) with a combination of Boolean logic operators (AND, OR, and NOT), Medical Subject Headings (MeSH), and keywords. A quality assessment was conducted to determine the relevance of the articles using JBI critical appraisal tools. Furthermore, several steps of assessment and evaluation were taken to select and analyze the relevant articles. Results . Of the 3912 articles identified through the electronic database search, 33 that met the inclusion criteria were included in the final analysis. The current study found that the global pooled prevalence of blood and body fluids among healthcare workers during career time and in the previous one year accounted for 56.6% (95% CI: 47.3, 65.4) and 39.0% (95% CI: 32.7, 45.7), respectively. Based on subgroup analysis by publication year, survey year, and World Health Organization regions, the highest prevalence of blood and body fluid exposure in the last 12 months was observed among articles published between 2004 and 2008 (66.3%), conducted between 2003 and 2008 (66.6%), and conducted in the Southeast Asia Region (46.9%). The highest career time prevalence was 60.6%, 71.0%, and 68.4% for articles published between 2015 and 2020, conducted between 2015 and 2019, and reported in the African region, respectively. Conclusion . The current study revealed a high prevalence of occupational exposure to blood and body fluids among healthcare workers and suggests the need to improve occupational health and safety services in healthcare systems globally.